Relationship of physical function with quality of life in older patients with acute heart failure. Issue 7 (10th April 2021) - Aladin, Amer I.; Whellan, David; Mentz, Robert J.; Pastva, Amy M.; Nelson, M. Benjamin; Brubaker, Peter; Duncan, Pamela; Reeves, Gordon; Rosenberg, Paul; Kitzman, Dalane W.
Abstract: Background: Older patients with acute decompensated heart failure (ADHF) have severely impaired physical function (PF) and quality of life (QOL). However, relationships between impairments in PF and QOL are unknown but are relevant to clinical practice and trial design. Methods: We assessed 202 consecutive patients hospitalized with ADHF in the multicenter Rehabilitation Therapy in Older Acute HF Patients (REHAB‐HF) Trial. PF measures included Short Physical Performance Battery (SPPB) and 6‐min walk distance (6MWD). Disease‐specific QOL was assessed by the Kansas City Cardiomyopathy Questionnaire (KCCQ). General QOL was assessed by the Short Form‐12 (SF‐12) and EuroQol‐5D‐5L. PF was evaluated as a predictor of QOL using stepwise regression adjusted for age, sex, race, and New York Heart Association class. Results: Participants were 72 ± 8 years, 54% women, 55% minority race, 52% with reduced ejection fraction, and body mass index 33 ± 9 kg/m 2 . Participants had severe impairments in PF (6MWD 185 ± 99 m, SPPB 6.0 ± 2.5 units) and disease‐specific QOL (KCCQ Overall Score 41 ± 21 and Physical Score 47 ± 24) and general QOL (SF‐12 Physical Score 28 ± 9 and EuroQol Visual Analog Scale 57 ± 23). There were modest, statistically significant correlations between 6MWD and KCCQ Overall, KCCQ Physical Limitation, and SF‐12 Physical Scores ( r  = 0.23, p  < 0.001; r  = 0.30, p  < 0.001; and r  = 0.24, p  = 0.001, respectively); and between SPPB and KCCQ Physical and SF‐12 Physical Scores ( r  = 0.20, p  = 0.004, and r  = 0.19, p  = 0.007, respectively). Both 6MWD and SPPB were correlated with multiple components of the EuroQol‐5D‐5L. 6MWD was a significant, weak predictor of KCCQ Overall Score and SF‐12 Physical Score (estimate = 0.05 ± 0.01, p  < 0.001 and estimate = 0.05 ± 0.02, p  = 0.012, respectively). SPPB was a significant, weak predictor of KCCQ Physical Score and SF‐12 Physical Score (estimate = 1.37 ± 0.66, p  = 0.040 and estimate = 0.54 ± 0.25, p  = 0.030, respectively). CONCLUSION: In older, hospitalized ADHF patients, PF and QOL are both severely impaired but are only modestly related, suggesting that PF and QOL provide complementary information and assessment of both should be considered to fully assess clinically meaningful patient‐oriented outcomes.